2010
DOI: 10.1111/j.1524-4725.2010.01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Carbon Dioxide Laser Therapy and Artificial Dermis Application in Plantar Warts: Human Papillomavirus DNA Analysis after Treatment

Abstract: A combination of CO₂ laser therapy and artificial dermis application effectively treated the majority of plantar warts after one treatment, with complete and rapid clearance and no persistent pain. The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…Our remission rate in the CO 2 laser group was 89%. This is very similar to the result that Mitsuishi found in his study [ 28 ]. Mitsuishi et al reported the only prospective non-blinded, non-randomized study on plantar warts to date.…”
Section: Discussionsupporting
confidence: 92%
“…Our remission rate in the CO 2 laser group was 89%. This is very similar to the result that Mitsuishi found in his study [ 28 ]. Mitsuishi et al reported the only prospective non-blinded, non-randomized study on plantar warts to date.…”
Section: Discussionsupporting
confidence: 92%
“…Early studies found a high recurrence rate and frequent complications, 21 although more recently higher success rates have been reported. 22 Pulsed dye lasers target blood vessels that are more prevalent in rapidly growing warts. The rate of response has been variable; in one study the response rates between conventional treatment and treatment using the pulsed dye laser were similar.…”
Section: Laser Ablationmentioning
confidence: 99%
“…Diğer bir çalışmada 31 hastadaki 35 plantar verrü lezyonuna CO2 lazer ile insizyon ve arkasından oluşan defekte artifisyal dermis uygulanması ile tek seans sonrası 35 lezyonda (%88,6) tam temizlenme saptanmış. 4 olguda (%11,4) lokal rekürrens saptanmış 48 .…”
Section: Diğer Tıbbi Endikasyonlarunclassified